The iceman cometh - O'Neill, Eugene, 1888-1953 (Yale University Press, 2020)
"A critical edition of O'Neill's most complex and difficult play, designed for student readers and performers. This critical edition of Eugene O'Neill's most complex and difficult play helps students and performers meet the work's demanding cultural literacy. William Davies King provides an invaluable guide to the text, including an essay on historical and critical perspectives; extensive notes on the language used in the play, and its many musical and literary allusions; as well as numerous insightful illustrations. He also gives biographical details about the actual people the characters are based on, along with the performance history of the play, to help students and theatrical artists engage with this labyrinthine work."--